2013
DOI: 10.3892/or.2013.2496
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Cathepsin B suppresses the proliferation and invasion of endometrial cancer

Abstract: Abstract. The molecular mechanism involved in the metastasis of endometrial cancer (EC) remains unclear. The lysosomal cysteine protease Cathepsin B has been implicated in the progression of various human tumors. In the present study, we assessed the expression of Cathepsin B and its functions in EC. Immunohistochemistry was used to examine Cathepsin B expression in 76 paraffin-embedded endometrial tumor tissues. Lentiviral packing short hairpin RNA (shRNA) was transfected into HEC-1A cells to build a stable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…ULK3 serves as a regulator in sonic hedgehog (SHH) signaling and autophagy in humans ( Young et al, 2009 ; Maloverjan et al, 2010 ). CTSB was found to participate in autophagy and immune resistance, which could be a potentially biomarker for various cancers ( Bao et al, 2013 ; Mirkovic et al, 2015 ; Bian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…ULK3 serves as a regulator in sonic hedgehog (SHH) signaling and autophagy in humans ( Young et al, 2009 ; Maloverjan et al, 2010 ). CTSB was found to participate in autophagy and immune resistance, which could be a potentially biomarker for various cancers ( Bao et al, 2013 ; Mirkovic et al, 2015 ; Bian et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin B is a lysosomal protease and is related to autophagy progression and p62 degradation [45]. Cancer studies have shown that cathepsin B is related to cancer cell proliferation [46], and its ability to break down the cell base membrane can increase cancer cell invasion. Our results show that ISL can decrease cathepsin B protein expression to suppress p62 accumulation, increasing autophagy-mediated apoptosis and decreasing cancer cell proliferation-related Ki67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins B and L are known to have opposite effects on cellular proliferation. For example, knockdown of cathepsin B with shRNA inhibits cell proliferation, migration and invasion in endometrial cancer cells (Bao et al , ). Similarly, downregulation of cathepsin L with RNA interference impairs cell proliferation.…”
Section: Discussionmentioning
confidence: 99%